TECHNOLOGY FOR IMPROVING MANAGEMENT COMPETENCE IN WOMEN TEACHERS (Universal International Scientific Journal, 2026)
The relevance of improving the management competence of female teachers in the leadership activities of women teachers in the context of modernizing the education system in the conditions of new Uzbekistan is scientifically substantiated. The article analyzes the theoretical foundations of the concept of "competence", its components, as well as gender stereotypes and other factors affecting the activities of female teachers-leaders. As a result of the research, a five-stage technology was developed based on person-oriented, gender-sensitive and innovative principles aimed at developing management competence in female teachers. In the practical part of the technology, modern methods such as coaching, mentoring, facilitation, "Agile management", "Design Thinking" are proposed. The importance of using T. Ehlers' "Leadership Motivation Test" at the diagnostic stage is substantiated. This technology serves to bring the quality and efficiency of education to a new level by systematically improving the transformational leadership skills of female teachers.
Keywords: Women educators, leadership competence, management competence, New Uzbekistan, gender-sensitive approach, transformational leadership, mentoring, coaching, Agile, Design Thinking, T. Ehlers test. .